Hubungan Peran Tenaga Kesehatan Dengan Kepatuhan Minum Obat Pada Lansia Yang Mengalami Hipertensi di Panti Werdha Kupang - Rihi, Pryati; S.K.Y. Kota, Melda; H. Pella, Yosin; F. Lagut, Yosefina; R. Pandie, Fance (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
Background: The role of nurses as health workers has a role as educators. Adherence to treatment for people with hypertension is important because hypertension is a disease that cannot be cured but must always be controlled or controlled so that complications such as heart failure, brain tissue damage and kidney failure do not occur. Objective: This study aims to determine the relationship between the role of health workers with adherence to taking medication in the elderly who experience hypertension at Panti Werdha Kupang. Research Methods: The research design used in this study is analytic observation, namely research that explains the relationship between variables through hypothesis testing. This type of research is Cross Sectional Analytic type. The sampling technique used by researchers used total sampling technique. Research Results: The results of the Chi-Square test analysis show that there is a relationship between the role of health workers and compliance with taking medication in the elderly who experience hypertension as evidenced by the p-value = 0.000, meaning that the p-value in this study is <0.05. Conclusion: There is a relationship between the role of health workers and compliance with taking medication in the elderly who experience hypertension at Panti Werdha Kupang.